Penguatan Moderasi Beragama bagi Aparatur Sipil Negara (ASN) Kementerian Agama dan Tokoh lintas Agama di Sumatera Utara - Rholand Muary (Pelita Masyarakat, 2022)
The purpose of this service is to strengthen religious moderation for the Ministry of Religion's State Civil Apparatus (ASN) and interfaith leaders. The method in this implementation is by training for 24 hours from 27-30 June 2022 at the Woong Ramee Hotel Serdang Bedagai. The results of this training activity produced 50 people as pioneers of religious moderation who would implement the values of religious moderation in their respective work environments. Religious moderation was initiated by the Ministry of Religion of the Republic of Indonesia as a response to the growing understanding of extremism, intolerant behavior and terrorism that can lead to national disintegration. As for the indicators in religious moderation, namely, first, national commitment where acceptance of the principles of the nation and state are contained in the 1945 constitution, second, tolerance, namely respecting differences and providing space for others to believe, express beliefs and express opinions, third, namely non-violence rejects the actions of a certain person or group using violent means, both physically and verbally in carrying out the desired changes and finally accepting the tradition in a friendly manner in line with religious behavior that does not conflict with the main teachings. The conclusion of this training is that it is hoped that ASN and interfaith leaders can ground the values of religious moderation in society.